Training for organizational transformation - Lynton, Rolf P; Pareek, Udai (New Delhi Sage, 2000)
While trainers and training institutions continue improving training methods, designs and materials,develop professional network and institutions, issues of fitting their efforts into overall change strategies funding and organizational support of scale
Contents: Pt.1. for policy- makers and chenge managers
Keywords: Employees-Training of; Organizational change